El Excentrico, 1967-03-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
March 20, 1967 [20 de marzo de 1967]. No volume or issue number. Cover has poster photos of two fashion models Mary Cavazos, whphas won the title of Miss Santa Clara and Margo Linda De Los Angeles, who has won the title of Miss San Jose. Both ladies are in regal attire and holding bouquet of flowers.